Penerapan Arsitektur Modern pada Aspek Tatanan Lahan dan Aspek Bangunan di Campus Da Fiocruz Ceara dan Bangkok International Preparatory & Secondary School - Dewi Syahputri Rahayu; Ika Ratniarsih (Tekstur (Jurnal Arsitektur), 2020)
Abstract. According to news, the city of Surabaya has issued around 20 athletes in swimming. Swimming has many benefits for the body such as reducing chronic diseases, heart health, etc. The number of water sports facilities built in the city of Surabaya is one of the containers with the aim to further popularize water sports and as a training center for swimming athletes in East Java. There are several categories of pools that have been available in the city of Surabaya such as water polo, beautiful jumping, fin swimming, etc. This facility is equipped with international standards based on the provisions of the Federation International de Natation (FINA) so that it can accommodate international swimming competition activities. However, of the many facilities that are available, almost all do not have special care on the building so that it looks less manicured as the age of the building. The use of methodologies with descriptive and case studies. Taking Literature case studies in Campus Da Fiocruz Ceara which has a land area of 103,683.00 m2 with a building area of 18,550.00 m2 and 43,147.00 m2. Having facilities such as Teaching Management Building, Research Laboratory Building, Infrastructure Building, Service Building, Auditorium, Service Kiosk, Security Cabin, Amphitheater, Bicycle Rack, Main Square and Parking Lot. In the second case study, the Bangkok International Preparatory Secondary School which has an area of 19,200 m2. It has facilities like in the first building there is an administration building that is connected with sports facilities (soccer field, athletic field 300 lines 4 lanes and 100 lines 4 straight lanes, tennis court, swimming pool 50 lanes 8 lanes, 2 indoor basketball courts, large sports hall , gymnastics room, local park), the second building has creative arts facilities (black box theater, music recording studio, ceramic room), and the third building has a 6-storey educational building facility (class room, library).Keywoards: Water Sport, Educational Facility, Training Abstrak. Menurut kabar berita, Kota Surabaya telah mengeluarkan atlit cabang olahraga renang sebanyak kurang lebih 20 orang. Olahraga renang memiliki banyak manfaat bagi tubuh seperti meredam penyakit kronis, menyehatkan jantung, dll. Banyaknya fasilitas olahraga air yang terbangun di Kota Surabaya merupakan salah satu wadah dengan tujuan untuk lebih mempopulerkan olahraga air serta sebagai wadah pelatihan atlit renang Jawa Timur. Terdapat beberapa kategori kolam yang telah tersedia di Kota Surabaya seperti polo air, loncat indah, fin swimming, dsb. Fasilitas ini dilengkapi dengan standar internasional berdasarkan ketentuan dari Federation International de Natation (FINA) sehingga mampu mewadahi kegiatan kompetisi renang tingkat internasional. Namun dari sekian banyak fasilitas yang tersedia hampir seluruh tidak memiliki perawatan khusus pada bangunan sehingga terlihat kurang terawat seiring berjalannya umur bangunan. Penggunaan metodologi dengan deskriptif dan studi kasus. Pengambilan Studi kasus literatur yang ada di Campus Da Fiocruz Ceara yang memiliki luas tanah 103.683,00 m2 dengan luas bangunan 18.550,00 m2 dan 43.147,00 m2 . Memiliki fasilitas seperti Gedung Pengajaran Manajemen, Gedung Pene litian Laboratorium, Gedung Infrastruktur, Gedung Layanan, Auditorium, Kios Layanan, Kabin Keamanan, Amphitheater, Rak Sepeda, Lapangan Utama dan Tempat Parkir. Pada studi kasus kedua yaitu Bangkok International Preparatory Secondary School yang memiliki luas area 19.200 m2. Memiliki fasilitas seperti pada bangunan pertama ada gedung administrasi yang terhubung dengan fasilitas olahraga (lapangan sepak bola, lapangan atletik 300 lajur 4 lajur dan 100 lajur 4 lintasan lurus, lapangan tenis, kolam renang 50 lajur 8 jalur, 2 lapangan basket indoor, aula olahraga besar, ruang senam, taman lokal), bangunan kedua ada fasilitas seni kreatif (Teater kotak hitam, studio rekaman music, ruang keramik), dan bangunan ketiga ada fasilitas bangunan pendidikan 6 lantai (ruang kelas, perpustakaan).Kata Kunci: Olah raga Air, Fasilitas Pendidikan, Pelatihan